Testicular tuberculosis can mimic a testicular tumor - Tim Jumbi; Robert Mugo; Leon Onkunya; Caroline Mwende; Francis Osawa; Swaleh Shahbal; David Kihiko Kuria (Elsevier, 2019)
Testicular tuberculosis (TB Orchitis) is a rare condition with a presentation that mimics testicular tumors. We present a rare case of TB orchitis in a 6-month old male infant who presented with a painless, firm left testicular mass that was initially managed as a testicular tumor but later confirmed to be TB orchitis after histological analysis. The aim of this report is to highlight the similarity of presentation between testicular TB and testicular tumors in children which may only be differentiated histologically therefore creating a diagnostic enigma. Keywords: Testicular tumor, Testicular tuberculosis, Histology